Symbols of Color in Classic Literature (Eurasian Scientific Herald, 2023)
This article discusses the basics of creating symbolic images associated with color in the works of Alisher Navoi, its place in Uzbek classical poetry, its role. Symbolic images associated with color serve to enhance the artistry, charm and impact of Uzbek poetry. In Alisher Navoi's poetry, color symbols have been studied using examples as a means of expressing ideas clearly, succinctly, and figuratively